“Isso aí seria o quê na tela?”: a inteligibilidade de imagens fetais ultrassonográficas coconstruída na e pela fala-em-interação - Frezza, Minéia (Universidade do Vale do Rio dos Sinos, 2019)
Beyond the advances ultrasound brought to obstetrics, it also made the socialization of the foetus possible. Thus, fetal ultrasound scans are considered as hybrid practices related to professional and social domains. However, anthropological research studies interested in these scans (CHAZAN, 2005, 2007, MITCHELL, 2001; TAYLOR, 2008) point out several communication problems between professionals and pregnant women during these encounters of science and family with the foetus/baby. These are the main complaints reported: (a) professionals do not explain the images; and (b) pregnant women, passive to the lack of explanation, do not request for information, or ask so much that end up “hindering” the service. Notwithstanding, there are few studies about how these interactions really happen (NISHIZAKA, 2014a, 2014b, 2013, 2011). Based on this scenario, this study aims at investigating how professionals and patients (do not) coordinate distinct semiotic fields (talk, gestures, images and resources from the ultrasound equipment) to achieve the multiactivities that constitute foetal ultrasound scans. As part of a bigger project interested in interactions in foetal medicine (OSTERMANN, 2013), this study analyzes 114 audio-video recorded ultrasound scans held in a ward specialized in high risk pregnancies assisted by the Brazilian Public Health System (SUS). The data analysis, sustained by Multimodal Conversation Analysis, evidences that the coordination among some ultrasound resources – as the pointer of the mouse and the actions of zooming in, stabilizing and freezing images, verbal and embodied references – constitutes the action of “showing” (with the meaning of “making someone see”) foetal images to the pregnant women. In these cases, the activity of performing the scan is suspended so that the activity of “socializing the foetus” can take place. On the other hand, there are instances in which the professionals describe foetal parts without coordinating verbal references with the image projected and with embodied reference. This “discoordination” among image, talk and gesture reveals a larger orientation to the professional domain, i.e., to the scan, but without disregarding the socialization of the being examined: the foetus that, beyond being medically assessed, is also introduced to the pregnant woman (and to the people who might accompany her) in the here-and-now interaction. When there are no explanations volunteered by the professionals, the pregnant women (and eventual companions) tend to initiate interactional sequences searching for information about the images and the foetal health. The results of this study point several technical contingencies, inherent to the context of foetal ultrasound, which can interfere in the achievement of answers deriving from the requests posed by the pregnant women. By means of the systematization of the interactional activities in this context, we aim to contribute to both the professional practices of dealing with the need of orchestrating several verbal, embodied and technical resources in the management of the hybridism that constitute ultrasound scans, and to the pregnant women and companions, who, at least in the context observed, handle the possibility of the having the ultrasound scan as the only opportunity to see their foetuses alive.
Keywords: Análise da conversa multimodal; Ultrassonografias fetais; Interação profissional da saúde-paciente; Multiatividade; Oferta e solicitação de informação; Multimodal conversation analysis; Fetal ultrasound; Health professional-patient interaction; Multiactivity; Information offer/request; ACCNPQ::Lingüística, Letras e Artes::Lingüística